Clerodane diterpenoids from Scutellaria formosana with inhibitory effects on NO production and interactions with iNOS protein. (December 2017) - Wang, Peixia; Liu, Feng; Yang, Xueyuan; Liang, Yue; Li, Shen; Su, Guochen; Jin, Da-Qing; Ohizumi, Yasushi; Xu, Jing; Guo, Yuanqiang
Abstract: A phytochemical study on Scutellaria formosana afforded five previously undescribed spiro-diterpenoids, scutellapenes A−E. The structures were elucidated on the basis of extensive 1D and 2D NMR spectroscopic data analysis, and the absolute configurations of these compounds were established by the time-dependent density functional theory (TDDFT) electronic circular dichroism (ECD) calculations. Scutellapenes B−E possess a spiro-diterpenoid skeleton. All of the compounds showed inhibitory effects on LPS-induced nitric oxide (NO) production in murine microglial BV-2 cells. The further molecular docking studies revealed that these bioactive compounds had strong interactions with the iNOS protein. Graphical abstract: Five previously undescribed spiro-diterpenoids, scutellapenes A−E, were isolated and characterized from Scutellaria formosana . All of the compounds showed inhibitory effects on NO production. Highlights: Five previously undescribed diterpenoids were isolated from Scutellaria formosana. The structures were elucidated by NMR data and ECD calculations. Scutellapenes B−E possess a spiro-diterpenoid skeleton. All of the compounds showed NO inhibitory effects. Molecular docking revealed interactions of bioactive compounds with iNOS protein.